CUL4B promotes aggressive phenotypes of renal cell carcinoma via upregulating c-Met expression. (January 2021) - Chen, Shouzhen; Wang, Yong; Chen, Lipeng; Xia, Yangyang; Cui, Jianfeng; Wang, Wenfu; Jiang, Xuewen; Wang, Jian; Zhu, Yaofeng; Sun, Shuna; Zou, Yongxin; Gong, Yaoqin; et al.
Highlights: CUL4B promotes proliferation, migration and invasion of RCC. CUL4B positively regulates c-Met expression in RCC at post-transcriptional level. c-Met inhibitor reverses the increased aggressiveness led by CUL4B overexpression in vitro and in vivo . Abstract: Cullin 4B (CUL4B), encoding a scaffold protein in Cullin RING ubiquitin-ligase complexes (CRL4B), is overexpressed and serves as an oncogene in various solid tumors. However, the roles and the underlying mechanisms of CUL4B in renal cell carcinoma (RCC) are still unknown. In this study, we demonstrated that CUL4B was significantly upregulated in RCC cells and clinical specimens, and its overexpression was correlated with poor survival of RCC patients. Knockdown of CUL4B resulted in the inhibition of proliferation, migration and invasion of RCC cells. Furthermore, we found that the expression of CUL4B is positively correlated with c-Met expression in RCC cells and tissues. Konckdown of c-Met or treatment with c-Met inhibitor, SU11274, could block the increase in cell proliferation, migration and invasion induced by CUL4B-overexpression. We also showed that CUL4B overexpression significantly accelerated xenograft tumor growth, and administration of SU11274 could also abrogate the accelerated tumor growth induced by CUL4B overexpression in vivo . These findings shed light on the contribution of CUL4B to tumorigenesis in RCC via activating c-Met signaling and its therapeutic implications in RCC patients.